Disability as Method: Interventions in the Habitus of Ableism through Media-Creation - Arseli Dokumaci (Disability Studies Quarterly, 2018)
In this article, I share and reflect on a research-creation video that introduces what I call 'disability as method' to critical disability and media studies. The video draws on a year-long visual ethnography, during which I collaborated with a blind and a physically disabled participant to explore the specificities of their mobility experiences in the city of Montreal. In making this video, I use the affordances of filming and editing in creative ways both to explore what access could mean to differently disabled people in the space of the city and to reimagine new possibilities of media-making informed by blindness gain. To this end, I introduce a new audio description (AD) technique by using stop-time as crip-time, and deploying AD not only as an accessibility feature but also as a blind intervention in the creative process of filmmaking itself.